THE INFLUENCE OF DIVERSITY ON EMPLOYEE SATISFACTION: A STUDY OF TERTIARY INSTITUTIONS IN THE NIGER DELTA REGION OF NIGERIA - Olusoji, Arubayi Damaro (jfpublisher, 2023)
This study investigated the influence of diversity on employee satisfaction: A study of tertiary institutions in the Niger Delta region of Nigeria. Discrimination is becoming widespread in the workplace and is harmful to organizations. Any modern business goals should always consist of abolishing all kinds of discrimination around their work environment and creating a positive environment that includes diversity. From a population of 13822, a sample of 389 respondents was chosen for the study. The simple percentage, mean & standard deviation, as well as Pearson Product Moment Correlation analytic methods, were used to analyze the data generated from fieldwork. It was discovered that there is no significant relationship between gender and organizational employee satisfaction, there is no significant relationship between age and employee satisfaction, and there is a relationship between ethnicity and employee satisfaction as well. There is a relationship between education and employee satisfaction. From the findings generated for this study, the researcher recommends that; organizations must consider workplace diversity as an important factor for the satisfaction of employees, organizations that are working in diversity will also focus on ethnicity and development of a common social awareness model, management of organizations should continue to take steps to manage the diversity elements for attaining the satisfaction of employees as well as remuneration, promotion and other motivational incentives awarded to employees should be based on merit rather than tribalism, educational qualifications or age/gender differences so as to establish equity in the workplace.